Are Patients at Risk for Recurrent Disease Activity After Switching From Remicade® to Remsima®? An Observational Study - Xue, Laixi; van Bilsen, K.; Schreurs, M. W. J.; van Velthoven, M. E. J.; Missotten, T. O.; Thiadens, A. A. H. J.; Kuijpers, R. W. A. M.; van Biezen, P.; Dalm, V. A. S. H.; van Laar, J. A. M.; Hermans, M. A. W.; Dik, W. A.; et al. (Frontiers in Medicine, 2020)
Background: Since the late ‘90s, infliximab (Remicade®) is being used successfully to treat patients with several non-infectious immune mediated inflammatory diseases (IMIDs). In recent years, infliximab biosimilars, including Remsima® were introduced in clinical practice. Aim: To investigate the interchangeability of Remicade® (originator infliximab) and its biosimilar Remsima® in patients with rare immune-mediated inflammatory diseases (IMIDs). Methods: This two-phased prospective open label observational study was designed to monitor the transition from Remicade® to Remsima® in patients with rare IMIDs. All included patients were followed during the first two years. The primary endpoint was the demonstration of non-difference in quality of life and therapeutic efficacy, as measured by parameters including a safety monitoring program, physicians perception of disease activity (PPDA) and patient self-reported outcomes (PSROs). Secondary outcomes included routine blood analysis, pre-infusion serum drug concentration values and anti-drug antibody formation. Results: 48 patients treated with Remicade® were switched to Remsima® in June-July 2016 and subsequently monitored during the first two years. The group consisted of patients with sarcoidosis (n=17), Behçet’s disease (n=12), non-infectious uveitis (n=11) and other diagnoses (n=8). There were no significant differences in PPDA, PSROs, clinical and laboratory assessments and pre-infusion serum drug concentrations between the groups. De novo anti-drug antibodies were observed in two patients. 7 patients with sarcoidosis and 5 with another diagnosis developed a significant disease relapse (n=7) or adverse events (n=5) within two years; 10 of these patients discontinued Remsima® treatment, one withdrew from the study and one received additional corticosteroid therapy. Conclusions: We observed no significant differences in PSROs, PPDA and laboratory parameters after treatment was switched from Remicade® to Remsima®. However, disease relapse or serious events were observed in 12 out of 48 patients when treatment was switched from Remicade® to Remsima®. The choice to switch anti-TNF alpha biologics in patients with rare IMIDs, particularly in sarcoidosis, requires well-considered decision-making and accurate monitoring due to a possibly higher incidence of disease worsening.